2021
DOI: 10.21037/tau-21-160
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative assessment of ureter perfusion after revascularization of transplanted kidneys using intravenous indocyanine green fluorescence imaging

Abstract: Background: Kidney transplantation is the most valuable renal replacement therapy. One of the most common urologic complications following kidney transplantation is ureter anastomosis leakage, which leads to high morbidity along with kidney graft loss. We hypothesized that indocyanine green (ICG) fluorescence videography can assess ureter perfusion after revascularization of transplanted kidneys.Methods: We conducted a prospective cross-sectional study in end-stage renal disease patients who underwent deceased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Such innovative designs contribute to the development of more effective and ingenious therapeutic strategies. 1,41–54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such innovative designs contribute to the development of more effective and ingenious therapeutic strategies. 1,41–54…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical ICG does not participate in body metabolism, has a high safety, and can provide accurate navigation during surgery. ICG can intuitively indicate the closure and permeability of the channel during vascular or intestinal surgery, evaluate the risk of anastomotic leakage, assess ureter perfusion after revascularization of transplanted liver 44 and kidneys, 45 and reduce the occurrence of postoperative complications. In microsurgery, blood vessel anastomosis, finger replantation, skin avulsion reconstruction and flap transplantation can be evaluated by NIR imaging.…”
Section: Electronic Excitabilities Of the Benzo(e)indole Conjugated S...mentioning
confidence: 99%
“…Fluorescence angiography is an emerging tool for this purpose that fulfills the requirements of allowing real-time, in situ, noninvasive, quantitative tissue perfusion measurements without exposing the patients to the relevant side effects. A recently published study comparing the results of intraoperative ureteral ICG perfusion assessment with histopathological findings of 31 sections of dissected ureters showed that ICG fluorescence angiography had a sensitivity of 100% and a specificity of 93% for the detection of ureteral ischemia [ 13 ]. According to the authors, optimal perfusion was only maintained in the proximal 14 cm of the ureters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that delayed graft function after kidney transplantation can be predicted intraoperatively by applying this technique [ 12 ]. A recently published study yielded encouraging results for the detection of early ureteral ischemia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In benign gynaecology, ICG can be used intravenously to assess the vascularisation of bowel anastomosis following segmental or disc resection ( Blanco-Colino and Espin-Basany, 2018 ) and of ureters following ureterolysis. ICG can also be instilled into the ureteric lumen using a ureteric catheter to identify the course of the ureter laparoscopically ( Kanammit et al, 2021 ). It can also be used instead of methylene blue (MB) in a number of scenarios (tubal patency test, bladder integrity test etc).…”
Section: Introductionmentioning
confidence: 99%